2005
DOI: 10.17221/4261-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical preservative and pressing of ensiled sugar-beet pulp on the quality of fermentation process

Abstract: This study deals with effects of pressing of ensiled sugar-beet pulp and of application of a chemical preservative on the quality of fermentation process. The experimental silages had a better sensory evaluation than the control ones. In silages treated chemically with a mixture of acids, statistically significantly (P < 0.01) higher dry matter content, lowest pH value, the value of lactic acid and the lowest content of all acids in dry matter were found after 180 days of storage from the beginning of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…Fraser et al (2001) reported that fermentation in pea silage was improved by the application of an inoculant containing Lactobacillus plantarum. The decrease in the production of lactic acid in unwilted silage caused by the chemical additive when compared to the control (P < 0.05) and inoculant (P < 0.001) treatments in the present study is in agreement with results published by Doležal et al (2005).…”
Section: Resultssupporting
confidence: 93%
“…Fraser et al (2001) reported that fermentation in pea silage was improved by the application of an inoculant containing Lactobacillus plantarum. The decrease in the production of lactic acid in unwilted silage caused by the chemical additive when compared to the control (P < 0.05) and inoculant (P < 0.001) treatments in the present study is in agreement with results published by Doležal et al (2005).…”
Section: Resultssupporting
confidence: 93%
“…These results were in agreement with those presented by Maravić et al indicated dry matter content of sugar beet pulp was 31.50% [6]. Additionally, Doležal et al reported dry matter of pressed sugar beet pulp was 23-24% and still containing small amount of sucrose 3.50% A small extent of sucrose is still expected to remain in the SBP after the extraction and pressing process [32]. Due to certain amount of residual sucrose in the SBP there are possibilities for emerging technologies as bioethanol production and biorefinery [33,34].…”
Section: Chemical Composition and Properties Of Biosorbentsupporting
confidence: 91%
“…Silage as roughage represents the basis of the beef cattle diet. To prepare good quality silage, all the technological procedures in best production practice should be carried out and all principles applied ( 5 ). The overarching ensiling principle consists in fast inactivation of enzyme systems and termination of microbial activity.…”
Section: Introductionmentioning
confidence: 99%